Applying Digital Technology in Exposing and Reintroducing a Forgotten Spice Plant - Marianto, Martinus Dwi (Institut Seni Indonesia Yogyakarta, 2024)
Many people in Yogyakarta like to eat nasi rawon, brongkos rice, or konro soup, whose main spice is kluwak. Kluwak is the seed content of the pucung tree fruit (pangium edule reinw), which is fermented to convert the cyanide content of the seeds into a safely edible spice. The results of observations and interviews state that many people in Yogyakarta (as a research area) no longer know the existence of the pucung trees at all, even though the fruit and kluwak are written in the Book of Wulang Reh and Wulang Sunu written by King Paku Buwana IV; written on the Javanese tembang 'Bapak Pucung.' The number and existence of pucung trees in Yogyakarta are increasingly rare and forgotten. If left in its current state, the pucung tree will become extinct. That was why the creative idea of researching and making a graphic novel about this spice tree emerged. The author collaborated with Aznar Zacky, Yohannes Jatmiko Yuwono, and Viyantoro Giri Saputa to present this graphic novel for publication and socialization. The goal is for the wider community to recognize black gold (kluwak), care for and preserve this species, and cultivate its natural products smartly and ecologically.